Cultural Representation of Babukung Dance Funeral Ceremony Ritual of The Dayak Tomun Tribe as a Media for Character Building through Local Wisdom - Fimeir Liadi; Jasiah Jasiah; Ummi Qudsiyah; Makmur Harun; Mahkamah Madi; Agon Agon; Nur Irma Yanti; Endang Andriyani (Millati: Journal of Islamic Studies and Humanities)
The Babukung/Habukung ritual is only believed by people who follow the Kaharingan religion, the community believes that the Babukung ritual can help the process of someone who has passed away, so the Babukung ritual is divided into three functions. Firstly, to summon the spirits of the ancestors. Second, to provide entertainment for the family. Third, to ease the financial burden on the family left behind. Babukung rituals are usually performed in the morning and at night. Bukung dance is still performed by Dayak people in 3 (three) villages Sudan, Karuing and Parit. Other villages are not heard of them performing Bukung dance, because they have been influenced by the entry of other religions, such as Christianity, Catholicism, Islam and Hinduism. Unlike these three villages, although they already have Christianity, Catholicism and Hinduism, they perform Bukung dance as a legacy of their ancestors. This research illustrates the phenomenon that exists in the midst of society, that the culture and behaviour of the community become special characteristics as a description of the uniqueness of the community itself. Traditional culture that has been rooted into beliefs continues to be carried out by the community as an embodiment of the heritage of their ancestors. This noble culture originating from the ancestors continues to be preserved, despite the onslaught of information technology that is increasingly intensive on human culture.